Prevalence and Potential Risk Factors for Occupational Low Back Pain Among Male Military Pilots: A Study Based on Questionnaire and Physical Function Assessment - Yang, Yizhuo; Liu, Shuai; Ling, Mengyu; Ye, Chaoqun (Frontiers in Public Health, 2022)
Objectives: Low back pain (LBP) has negative implications for the military's combat effectiveness. This study was conducted to determine the prevalence and risk factors of LBP among pilots through a questionnaire and physical function assessments. Methods: Data on the demographic and occupational characteristics, health habits, physical activity, and musculoskeletal injuries of 217 male pilots (114 fighter, 48 helicopter, and 55 transport pilots) were collected using a self-reported questionnaire and physical function assessments. Results: LBP prevalence was 37.8% in the total cohort and 36.0, 45.8, and 34.5% among fighter, helicopter, and transport pilots, respectively. Multivariate regression analysis revealed that the risk factors significantly associated with LBP were neck pain [odds ratio (OR): 3.559, 95% confidence interval (CI): 1.827–6.934], transversus abdominis activation (OR: 0.346, 95% CI: 0.172–0.698), and hip external rotator strength (OR: 0.001, 95% CI: 0.000–0.563) in the total cohort; neck pain (OR: 3.586, 95% CI: 1.365–9.418), transversus abdominis activation (OR: 0.268, 95% CI: 0.094–0.765), hip external rotator strength (OR: 0.000, 95% CI: 0.000–0.949), and weekly flying hours (OR: 3.889, 95% CI: 1.490–10.149) in fighter pilots; irregular strength training (OR: 0.036, 95% CI: 0.003–0.507) and hip external rotator strength (OR: 0.000, 95% CI: 0.000–0.042) in helicopter pilots; and neck pain (OR: 6.417, 95% CI: 1.424–28.909) in transport pilots. Conclusions: High volume flight schedules and weak core muscle functions have significant negative effects on pilots' back health. LBP is commonly associated with high weekly flying hours, worsening neck pain, transversus abdominis insufficient activation, and reduced hip extensor/rotator strength. Risk factors vary among pilots of different aircraft. Thus, specific core muscle training would be especially important for military pilots.